Luteal-phase ovarian stimulation vs conventional ovarian stimulation in patients with normal ovarian reserve treated for IVF: a large retrospective cohort study - Wang, Ningling; Wang, Yun; Chen, Qiuju; Dong, Jing; Tian, Hui; Fu, Yonglun; Ai, Ai; Lyu, Qifeng; Kuang, Yanping (Clinical endocrinology (Oxford), 2016)
Summary Objective We have previously reported a new luteal‐phase ovarian stimulation (LPS) strategy for infertility treatment. The purpose of this study was to systematically assess the efficiency and safety of this strategy by comparing it with conventional ovarian stimulation protocols. Design Retrospective cohort study. Subjects Patients with normal ovarian reserve undergoing ovum pick‐up (OPU) cycles between April 2012 and September 2013 were enrolled: 708 patients underwent the LPS protocol compared with 745 patients who underwent the mild treatment protocol and 1287 patients who underwent the short‐term protocol. Measurements Number of mature oocytes retrieved and top‐quality embryos obtained, implantation rate, pregnancy rate, live birth and ongoing pregnancy rate and neonatal outcomes. Results The numbers of mature oocytes retrieved and top‐quality embryos obtained per OPU cycle were significantly increased in the LPS group (10·9 ± 7·6 and 4·6 ± 4·3, respectively) compared with the mild treatment group (3·7 ± 3·0 and 1·8 ± 1·8, respectively, both P < 0·001) or the short‐term group (9·1 ± 5·5 and 3·7 ± 3·1, respectively, both P < 0·001). Moreover, the total gonadotrophin used was also the highest in the LPS group. No significant differences were identified in the implantation rate (35·5% vs 34·8%, P > 0·05), pregnancy rate (46·2% vs 43·7%, P > 0·05) or live birth and ongoing pregnancy rate (44·4% vs 41·7%, P > 0·05) per frozen‐thawed embryo transfer (FET) cycle in the LPS and mild treatment groups, respectively. However, the LPS protocol achieved a higher implantation rate (35·5% vs 31·8%, P = 0·012), pregnancy rate (46·2% vs 41·9%, P = 0·041), and live birth and ongoing pregnancy rate (44·4% vs 39·2%, P = 0·012) compared with the short‐term protocol. Neonatal outcomes in the LPS group were similar to the other two groups. Conclusions The available data suggest that LPS is a feasible strategy for infertility treatment and complements the available follicular‐phase ovarian stimulation strategies.